Analysis of Leading Economic Sectors in Jayapura City - Charley M. Bisai; Risa Alifia Maharani; Sarlota A. Ratang; Balthazar Kreuta; Antonia Klara; Marsi Adi Purwadi (International Journal of Science and Society, 2025)
This study aims to analyze the sectoral classification in Jayapura City and determine the economic sectors that can become the mainstay sectors in the Jayapura City economy during the period 2011-2023. The analysis is conducted based on Gross Regional Domestic Product (GRDP) data based on sector contributions to growth, the Growth Ratio Model, and overlay analysis. Data are obtained from official sources, such as publications of the Central Statistics Agency and regional economic reports. Based on the Growth Ratio Model (MRP), sectors in Jayapura City can be classified into several categories. Sectors that fall into classification I, or "dominant growth," include electricity and gas procurement, construction, wholesale and retail trade, information and communication, financial services and insurance, real estate, and government administration. Meanwhile, sectors such as agriculture, manufacturing industry, and corporate services are in classification II, showing prominent growth at the provincial level but less developed at the district level. The mining and quarrying sector falls into classification IV, with low growth at both the provincial and district levels. Furthermore, based on the overlay analysis, it was found that the mainstay sectors in the Jayapura City economy are construction and wholesale and retail trade, which show significant contributions to regional economic growth. Other potential sectors include government administration, information and communication, and financial services and healthcare, which have shown stable growth and significant contributions. With policies supporting these sectors, such as infrastructure improvements, service modernization, and strengthening the logistics system, these sectors can serve as key pillars of sustainable economic growth in Jayapura City.